1991
DOI: 10.1111/j.1399-0039.1991.tb02029.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA class II‐associated genetic susceptibility in multiple sclerosis: A critical evaluation

Abstract: Multiple sclerosis (MS) has, since the 1970s, been known to be associated with the HLA-Dw2 and -DR2 specificities in Caucasian Europeans and North Americans. By the use of genomic typing techniques, the association has been specified to be with the DRw15,DQw6,Dw2, i.e. the DRB1*1501-DQA1*0102-DQB1*0602 haplotype. A significant DPw4 association in Scandinavian MS patients has been described in one report. However, this association has not been confirmed in several subsequent studies with patients from the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
191
2
8

Year Published

1993
1993
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 441 publications
(206 citation statements)
references
References 81 publications
5
191
2
8
Order By: Relevance
“…In a follow-up case-control study of 179 Swedish patients and 250 controls, these investigators confirmed the association with HLA-DRw15 (HLA-DRB1*1501) and MS in both PPMS and RRMS patients relative to healthy controls (OR ¼ 3.99, p < 0.0001) (Olerup and Hillert, 1991). When the 36 PPMS patients were considered separately, the association with HLA-DRw15 persisted (OR ¼ 3.27, p ¼ 0.001), as did the association in RRMS (OR ¼ 4.2, p < 0.0001).…”
Section: Human Leukocyte Antigensmentioning
confidence: 72%
“…In a follow-up case-control study of 179 Swedish patients and 250 controls, these investigators confirmed the association with HLA-DRw15 (HLA-DRB1*1501) and MS in both PPMS and RRMS patients relative to healthy controls (OR ¼ 3.99, p < 0.0001) (Olerup and Hillert, 1991). When the 36 PPMS patients were considered separately, the association with HLA-DRw15 persisted (OR ¼ 3.27, p ¼ 0.001), as did the association in RRMS (OR ¼ 4.2, p < 0.0001).…”
Section: Human Leukocyte Antigensmentioning
confidence: 72%
“…A similar negative result was more recently reported by MALIARIK et al [61] in 69 African-American patients with sarcoidosis, in which the frequency of HLA-DPGlu 69 was only slightly increased over that in controls. The same authors did, however, report a weak association for Val 36 (OR=2.30) and for Asp 55 (OR=2.03), suggesting that such residues may contribute to sarcoidosis susceptibility in African-Americans. In contrast, in 41 British subjects with sarcoidosis, LYMPANY et al [62], although unable to find an association with HLA class II alleles or to confirm the association with the DPB1 position 55, reported that 26/47 sarcoid subjects had DPB1*Glu 69 alleles, this being a significantly higher frequency than that in the controls (p<0.02).…”
Section: Hla-dpb1 Gene and Sarcoidosismentioning
confidence: 89%
“…3 Within the MHC, the human leukocyte antigen (HLA) DRB1*1501-DRB5*0101-DQA1*0102-DQB1*0602 haplotype has a pre-eminent role, especially for populations of Northern European descent. [4][5][6][7] However, there is now robust, validated evidence that other variants within the MHC have independent roles in rendering individuals susceptible to MS, 8 and there is evidence for a role of the MHC in age at onset 9 and disease course. 10,11 Many studies have used clinical measures of severity to explore this aspect, but MRI-derived measures (such as brain atrophy and T 2 -weighted lesion volume or T2LV) appear to be more sensitive in capturing the course of disease, particularly in the early years after symptom onset.…”
Section: Introductionmentioning
confidence: 99%